Dinamika Kekerasan Penonton Olahraga: Pemicu,dampak dan Solusi - Alvin Barasa; Bani Pratama; Adriano Sitompul; Rahma Dewi (Pusat Riset dan Inovasi Nasional, 2024)
This study explores the factors that trigger violent behavior among sports spectators and the role of media and social media in shaping such behavior. Data were obtained through in-depth interviews with five informants: Pipin, Evelyn, Faizma, Celci, and Stefanus. The results of the study indicate that excessive fanaticism, provocation, referee decisions that are considered unfair, and alcohol consumption are the main triggers. Media and social media have a major influence on the formation of public opinion but also contribute to negative behavior. This study recommends strict sanctions, education, and responsible media management as solutions.